(untitled) - Burian, Peter K. (San Francisco, 2004)
This book is suited for people with little understanding of photography who are looking to get started with a digital camera. It guides techniques for getting scans of exceptional quality, whether you’re scanning prints, slides, or negatives... and tips on optimizing your images for use in e-mail, online albums, and web pages.
Keywords: Photography,Nhiếp ảnh; Digital techniques,Kỹ thuật số